Investigation of noise threats and their impact on hearing in selected schools – a pilot study - Kotus, Joseph; Kostek, Bożena (Archives of Acoustics, 2006)
Noise measurements conducted in selected schools in Gdańsk area are presented in this paper. The main aim of this research was to determine noise threats at schools. Some objective measurements of the acoustic climate were performed employing a noise monitoring station engineered at the Multimedia System Department, Gdańsk University of Technology. Simultaneously, subjective noise annoyance examinations were carried out among pupils in chosen schools. The survey includes a noise analysis in places of residence, music preferences and preliminary hearing tests results taken after the exposure to noise during breaks. Hearing tests employing a distortion product otoacoustic emission (DPOAE) method, have been performed twice – before and after the exposure to noise. The noise dose analysis based on average time spent by a pupil at school is also presented. The obtained results reveal that an unfavorable noise climate occurred in surveyed schools. This was also confirmed by the results of the subjective examinations. The conducted hearing tests did not reveal essential changes in the cochlea activity of examined pupils. This means that the noise during breaks and physical exercises did not constitute a risk to their hearing system. However, it may be considered as an essential source of annoyance.